Effect of best practice advisory on the administration of contraindicated medications to hospitalized patients with Parkinson’s disease and related disorders - Chunga, Natalia; Amodeo, Katherine; Braun, Melanie; Valdovinos, Blanca Y.; Richard, Irene H. (Frontiers in Aging Neuroscience, 2023)
Objective To determine the effect of a Best Practice Advisory (BPA) on the ordering and administration of contraindicated dopamine blocking agents (DBA) to hospitalized patients with Parkinson’s disease (PD) and related disorders. Background Patients with PD are more likely to require hospitalization and are at increased risk of complications. Administration of contraindicated DBA contributes to worsened outcomes in this patient population. Electronic medical record (EMR) warnings (also referred to as BPA) have been proposed as a way to prevent the administration of contraindicated medications. Methods A BPA was launched in January 2020 within the University of Rochester EMR system, which alerts the provider when a contraindicated DBA is ordered in hospitalized patients with PD and related disorders. Patients with PD and related disorders hospitalized at two hospitals affiliated to the University of Rochester during a time period before (t1: 1/1/2019–1/1/2020) and after (t2: 1/8/2020–1/8/2021) the implementation of the BPA were included in this study. Epic SliderDicer was used to collect the data from the University of Rochester EMR. The number of patients who had contraindicated DBA orders and administrations in both time periods, and the number of patients who had the BPA triggered during t2 were obtained. We compared the results before and after the implementation of the BPA. Results 306 patients with PD and related disorders were hospitalized during t1 and 273 during t2. There was significantly less percentage of patients who had contraindicated DBA orders (41.5% in t1 vs. 17.6% in t2) and patients who had contraindicated DBA administrations (16% in t1 vs. 8.8% in t2) during t2 (p < 0.05 for both comparisons). There was no significant difference between the percentage of patients who had contraindicated DBA orders in t1 and patients with attempted orders (BPA triggered) in t2 (p = 0.27). Conclusion The results of this study increase the evidence of the potential benefit of EMR warnings for the optimization of inpatient medication management in patients with PD and related disorders. In particular, our results suggest that EMR warnings help reduce the administration of contraindicated medications, which is a known contributing factor for hospital complications in this patient population.